Osteoporosis: a problem still faulty addressed by the Romanian healthcare system. Results of a questionnaire survey of people aged 40 years and over - Jianu, Narcisa; Buda, Valentina Oana; Căpățână, Denisa; Muntean, Călin; Onea, Teodor Nicolae; Jivulescu, Maria Anastasia; Teodor, Ana; Romanescu, Mirabela; Udrescu, Lucreția; Groza, Vlad; Udrescu, Mihai; Buzatu, Alina Ramona; et al. (Frontiers in Medicine, 2024)
We aimed to investigate the knowledge and awareness level of osteoporosis, its risk factors, the possible causes of underdiagnosis, as well as the preventive measures and lifestyle behavior of the Romanian population.A non-interventional, cross-sectional study was performed, consisting of an in-person survey, in 10 pharmacies located in both urban and rural settings in Romania. The survey was distributed to patients ≥40 years old. Results: Of 189 respondents, 78.8% were women, the majority age group being 60-69 (31.7%) and 50-59 (30.7%) years old and coming from urban areas (69.3%). Although 75.1% of participants declared knowing about osteoporosis, having a moderate level of knowledge, and women being more aware of the pathology, 77.2% have never performed a DXA test. Moreover, participants already diagnosed with osteoporosis did not show a better disease knowledge than those without a diagnosis. Nearly half of the respondents did not know that a family history of the disease increases the risk of developing it and 60% of them thought that symptoms may develop before a fracture occurs. The preventive strategies tend to be disregarded and thus, underused. Moreover, 42.85% of participants reported being diagnosed with osteoporosis, do not undergo treatment, although they are aware of the existence of effective strategies. The dataset was used to build a participant compatibility network. The network's clustering revealed six relevant communities, which are not correlated with questionnaire results but reflect the patterns of feature associations.Preventive and therapeutic osteoporosis education programs are urgently needed in the Romanian population to decrease disability and high mortality risks and thus, to improve the quality of life.